Disease-related expression of the IL6/STAT3/SOCS3 signalling pathway in ulcerative colitis and ulcerative colitis-related carcinogenesis. Issue 2 (18th November 2009) - Li, Yi; de Haar, Colin; Chen, Min; Deuring, Jasper; Gerrits, Monique M; Smits, Ron; Xia, Bing; Kuipers, Ernst J; van der Woude, C Janneke
Abstract : Background: Mouse models have shown that interleukin (IL)6 stimulates survival, proliferation and progression to cancer of intestinal epithelial cells via activation of signal transducers and activators of transcription 3 (STAT3). Objective: To investigate the expression of IL6/phosphorylated STAT3 (p-STAT3)/suppressor of cytokine signalling 3 (SOCS3) in biopsy specimens from patients with ulcerative colitis (UC) and UC-related colorectal cancer (CRC) progression. Methods: Biopsy specimens from patients with inactive UC (n=18), active UC (n=28), UC with low-grade dysplasia (LGD) (n=9), UC with high-grade dysplasia (HGD) (n=7), UC-CRC (n=11) and sporadic CRC (n=14) were included. Biopsy specimens (n=9) from patients without colonic abnormalities served as control. The protein expression of IL6, p-STAT3 and SOCS3 was determined immunohistochemically. Results: Patients with active UC had significantly more IL6 and p-STAT3-positive epithelial cells than both patients with inactive UC and controls (strong positive IL6: 53.6%, 11.1% and 0%, respectively; p-STAT3: 64.3%, 22.2% and 11.1%, respectively; all p≤0.012). SOCS3-positive cells were significantly increased in colonic epithelium of both inactive and active UC compared with controls (strong positive: 94.4%, 96.4% and 11.1%, respectively; both p<0.001). In dysplasia and cancer, significantly more epithelial cells expressed IL6 and p-STAT3 compared with controls (strong positive IL6: 72.7% and 0% respectively; p-STAT3: 54.5% and 11.1%, respectively; both p<0.05), whereas the proportion of SOCS3-positive cells in this progression reduced (LGD 33.3%; HGD 14.3%; UC-CRC 9.1%). In addition, methylation of the SOCS3 gene was detected in epithelial cells from UC-CRC biopsy specimens. Conclusion: The importance of IL6/p-STAT3 in patients with inflammation-induced CRC was demonstrated. Moreover, SOCS3 may be involved in UC pathogenesis and the absence of SOCS3 seems critical for CRC progression.